Persepsi Masyarakat Mengenai Alih Fungsi Lahan Kawasan Caringin Tilu Kecamatan Cimenyan Kabupaten Bandung - Budi Kurniadi (Lembaga Penelitian Universitas Langlangbuana, 2019)
Transfer of land functions is still a common problem in some areas. Caringin Tilu is located in the hills of Mount Manglayang, East Bandung, Cimenyan Subdistrict, Bandung Regency is a conservation area that has experienced rapid development, which was productive agricultural land into a tourist area with little regard for preservation of hydrological functions, especially for critical land. The purpose of this study is to find out, describe in depth and analyze people's perceptions about land use change and its causal factors and impacts. The research method used is a qualitative research method that emphasizes the development of appreciation and motivation of what people do with the assumption to understand human behavior by first understanding the object under study.The results of this study indicate that community perceptions about land use change are determined with different perspectives relating to benefits and interests, so community perceptions are very subjective. The perception of the community, especially smallholders and non-landowners, looks very different from the community members who have an interest in responding to the development of the area in terms of its benefits. The development of this region is not all viewed positively, because it gives birth to new problems.Transfer of land functions is still a common problem in some areas. Caringin Tilu is located in the hills of Mount Manglayang, East Bandung, Cimenyan Subdistrict, Bandung Regency is a conservation area that has experienced rapid development, which was productive agricultural land into a tourist area with little regard for preservation of hydrological functions, especially for critical land. The purpose of this study is to find out, describe in depth and analyze people's perceptions about land use change and its causal factors and impacts. The research method used is a qualitative research method that emphasizes the development of appreciation and motivation of what people do with the assumption to understand human behavior by first understanding the object under study.The results of this study indicate that community perceptions about land use change are determined with different perspectives relating to benefits and interests, so community perceptions are very subjective. The perception of the community, especially smallholders and non-landowners, looks very different from the community members who have an interest in responding to the development of the area in terms of its benefits. The development of this region is not all viewed positively, because it gives birth to new problems.